The COVID-19 pandemic’s impact on employment of population in Russia (based on the materials of the Vologda region) - A. V. Popov (Publishing House of the State University of Management, 2021)
The article analyses the consequences of the COVID-19 pandemic for employment of the population in Russia. The range of issues studied is largely based on previous studies in this area and covers the problems of the spread of remote work, the growth of unemployment, the decline in wages and working hours. Special attention is paid to the sustainability of workers, as well as the state and fulfilment of their labor potential. The information base of the research is presented by a sociological survey conducted on the territory of the Vologda region of Russia in a monitoring mode. The results of the analysis are consistent with the key negative trends in employment during the pandemic: many employees have faced violations of labor rights, delays and non-payment of salaries, the need to find another job. With the backdrop of the deteriorating quality of labor potential, an increase in the pressure of work is identified, which can contribute to the exacerbation of occupational diseases. The paper concluded that it is necessary to find the optimal balance between the nation’s health and economic growth.